Theravada Traditions: Buddhist Ritual Cultures in Contemporary Southeast Asia and Sri Lanka, by John Clifford Holt. (31st December 2019) - Harris, Elizabeth
Abstract : Theravada Traditions: Buddhist Ritual Cultures in Contemporary Southeast Asia and Sri Lanka, by John Clifford Holt. University of Hawai'i Press. 2017. 391pp. Hb. 68, ISBN-13: 978-0-82486-780-5.